T Cell-based RAS Activity and Insulin Levels in Obese Subjects with Low Grade Inflammation - Coppo, M; Bandinelli, M; Chiostri, M; Modesti, P A; Poggesi, L; Boddi, M (The American journal of the medical sciences, 2022)
Obesity is a major contributor to inflammation and oxidative stress that are key underlying causes for insulin resistance (IR) and diabetes. Accumulated evidence suggest that RAS may serve as a strong link between IR and obesity. We investigated RAS activity in circulating T cells by obese subjects with and without angiotensin (Ang) II stimulation in presence or not of IR and of low-grade inflammation. We studied 29 obese and 10 healthy subjects. After T-lymphocytes isolation, mRNAs for angiotensin converting enzyme (ACE) and angiotensin 1-receptor (AT1-R) were quantified by reverse transcription polymerase chain reaction (RT-PCR). High-sensitivity C-reactive protein (hs-CRP), insulin and inflammatory cytokines serum levels, plasma renin activity (PRA) and ACE activity in cell pellet and supernatant, and angiotensin (Ang) II T cell content were also measured. Under baseline conditions, RAS gene expressions, ACE activity and Ang II levels in T cells, but not PRA, of obese subjects with or without IR and with or without hs-CRP ≥3mg/dl were higher than in controls (p < 0.05). The increase in all parameters induced by Ang II was significantly higher in T cells from the obese subjects with hs-CRP ≥3 mg/dl than in controls or in the obese subjects with hs-CRP <3 mg/dl. In the obese subjects with low grade inflammation and IR, the cytokine serum levels and T cells RAS gene expression was inversely correlated with insulin serum concentration. Low grade inflammation amplifies the T cell RAS response to Ang II stimulation. T cell RAS gene expressions and serum levels of inflammatory cytokines were inversely related with insulin serum concentration. A protective role of insulin towards the development of inflammatory events can be hypothesized.